Fallout eaudiobook Spies, superbombs, and the ultimate cold war showdown. - Sheinkin, Steve (Listening Library, 2021)
New York Times  bestselling author Steve Sheinkin   presents a follow up to his award-winning book  Bomb: The Race to Build—and Steal—the World's Most Dangerous Weapon , taking listeners on a terrifying journey into the Cold War and our mutual assured destruction. As World War II comes to a close, the United States and the Soviet Union emerge as the two greatest world powers on extreme opposites of the political spectrum. After the United States showed its hand with the atomic bomb in Hiroshima, the Soviets refuse to be left behind. With communism sweeping the globe, the two nations begin a neck-and-neck competition to build even more destructive bombs and conquer the Space Race. In their battle for dominance, spy planes fly above, armed submarines swim deep below, and undercover agents meet in the dead of night. The Cold War game grows more precarious as weapons are pointed towards each other, with fingers literally on the trigger. The decades-long showdown culminates in the Cuban Missile Crisis, the world's close call with the third―and final―world war.